(3QhVI GdcGajs - (3Gdcdjfj, CHh LYaQ, Gdcdjfj, eMeO Hf jYbhH Hf ESMGb, J (B329(3g` (B941(3es ((3Rjf GdYGHOjfs)
(3ChdgG (B:s
(3ChdgG(B: (3CeG HYO, aGSCdhG Gddg QHce GdYGajI hYdjce HGdOYI hGdhbGQ hGdScjfI hYdjce HGdMjGA hGdJfRg YeG JfRg Yfg GdUGdMhfs
(3BNQgG (B:s
(3BNQgG(B: (3hGdMeO ddg dG JONd CMOG aj VdGdI hdG jNQLg ef gOi, Ef GdOfjG dG JPgH MJi jHYK Gddg YR hLd QLdG efG Cgd GdHjJ jYed HcJGH Gddg YR hLd dG jQi ajce efcQG EdG CfcQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 145s
(3GdPQjYI, L (B11: 217s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis